Possibilities of fibre-reinforced cement composites using to restore the water supply pipeline - Savva Viktorovich Skorikov; Viktor Vasil’evich Shishkin; Alina Vladimirovna Akinshina (Наука. Инновации. Технологии)
General approach to the design of the composition of the fibrous mixtures, of a kind used for the application of maintenance of the coating on the inner surface of the pipe, is given in the article. Recommendations are given on the opportunities to use a certain type of fiber when restoring.